The neurovascular extracellular matrix in health and disease. Issue 7 (April 2021) - Logsdon, Aric F; Rhea, Elizabeth M; Reed, May; Banks, William A; Erickson, Michelle A
The blood–brain barrier (BBB) is a vital interface that supports normal brain functions. Endothelial cells (ECs) are the main component of the BBB and are highly specialized to govern the transfer of substances into brain. The EC lumen is enmeshed with an extracellular matrix (ECM), known as the endothelial glycocalyx layer (EGL). The lumen-facing EGL is primarily comprised of proteoglycans (PGs) and glycosaminoglycans (GAGs), which function as the first line of defense for blood-to-brain transfer of substances. Circulating factors must first penetrate the EGL before interacting with the EC. The abundance and composition of the PG and GAGs can dictate EGL function, and determine which circulating substances communicate with the ECs. The EGL can interact with circulating factors through physio-chemical interactions with the EC. Some disease states reveal a "thinning" of the EGL that may increase EC interactions with components of the systemic circulation and alter BBB function. EGL changes may also contribute to the cognitive complications of systemic diseases, such as sepsis and diabetes. For decades, researchers have measured how genetic and environmental factors influence the peripheral EGL constituents; however, much less is known about the neurovascular EGL. In this mini-review, we introduce components of the EGL and innovative ways to measure their abundance and composition that may contribute to BBB dysfunction.